Ultrasound evaluation of female reproductive system in free ranging Giant Anteater (Myrmecophaga tridactyla): Case report - Maronezi, M. C. [UNESP]; Lemos, G. G. [UNESP]; Lima, F. H. [UNESP]; Izique, L. M. [UNESP]; De Santi, M. [UNESP]; Couto, C. [UNESP]; Pereira, T. M.; Uscategui, R. A.R.; Minto, B. W. [UNESP]; Werther, K. [UNESP]; Feliciano, M. A.R. [UNESP] (FapUNIFESP (SciELO), 2020)
An adult, female, 31kg body weight, free range Myrmecophaga tridactyla was referred for medical consultation due to apathy, dehydration, intense flatulence and fetid stools. The animal was submitted to chemical restraint and physical examination, blood count, fecal analysis, and vaginal cytology and abdominal ultrasonography were performed. Good nutritional status and clinical variables within the normal range were observed at physical examination. At vaginal cytology leukocytes, spermatozoa and a large proportion of cornified cells (superficial) were observed, indicating estrus and recent copula. At ultrasound examination it was possible to locate, identify, evaluate and measure the ovaries and the uterine structures, cervix, body, lumen, myometrium and endometrium, a fact never reported in the literature for this species. These data can be used as reference for clinical evaluation of the reproductive tract in Myrmecophaga tridactyla females considered vulnerable species, for the diagnosis of reproductive pathologies, biotechnologies application or estrous cycle evaluation.
Keywords: Estrous cycle; Ovary; Uterus; Xenarthra